Case Report: Isolated facial and trigeminal nerve palsy without ataxia in anti-GQ1b antibody syndrome secondary to Mycoplasma pneumonia - Deng, Shuwen; Yin, Lihong; Lu, Wei; Ouyang, Song; Yin, Weifan (Frontiers in Immunology, 2022)
The presence of anti-GQ1b antibodies in serum or cerebrospinal fluid is a diagnostic indicator of the Miller–Fisher variant of Guillain–Barré syndrome (GBS), whereas anti-GQ1b antibody syndrome is rarely presented as acute bilateral pain in the cheeks and masticatory muscle fatigue without ophthalmoplegia, ataxia, or limb weakness. Here, we report a case of a female patient diagnosed with GBS characterized only by the involvement of the facial and trigeminal nerves who was positive for serum anti-GQ1b antibodies secondary to Mycoplasma pneumoniae infection. The patient was treated with macrolide antibiotics and neurotrophic drugs, and her symptoms were significantly alleviated after 1 month. This case indicates a new clinical presentation of GBS and anti-GQ1b antibody syndrome with a differential diagnosis of multiple cranial nerve damage of which neurological physicians should be aware. Positive anti-GQ1b antibodies secondary to infection were observed in this case, and antibiotic treatment resulted in a favorable prognosis. The specific underlying mechanism requires further investigation.